2011
DOI: 10.3402/ejpt.v2i0.5694
|View full text |Cite
|
Sign up to set email alerts
|

A randomised comparison of cognitive behavioural therapy (CBT) and eye movement desensitisation and reprocessing (EMDR) in disaster-exposed children

Abstract: Background Building on previous research with disaster-exposed children and adolescents, a randomised clinical trial was performed in the treatment of trauma-related symptoms. In the current study two active treatments were compared among children in a broad age range and from a wide diversity of ethnic populations.Objective The primary aim was to compare the effectiveness and efficiency of Cognitive Behavioural Therapy (CBT) and Eye Movement Desensitisation and Reprocessing (EMDR).Design Children (n=52, aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 29 publications
4
98
0
1
Order By: Relevance
“…Hence studies that directly compared these disparate treatments such as (Devilly & Spence, 1999;Taylor et al, 2003) were not included in our analysis. Numerous other studies also did this (de Roos et al, 2011;Ironson, Freud, M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…Hence studies that directly compared these disparate treatments such as (Devilly & Spence, 1999;Taylor et al, 2003) were not included in our analysis. Numerous other studies also did this (de Roos et al, 2011;Ironson, Freud, M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…Any treatment effect observed could also be due to general contact aspects of a psychosocial intervention. However, it has repeatedly been shown that EMDR is as effective as TF-CBT or even more effective (De Roos et al, 2011, 2017; Diehle et al, 2014; Rodenburg et al, 2009). It is also possible that some of the participants in the care-as-usual group will nonetheless search psychological treatment during the assessment period.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to TF-CBT, ‘EMDR does not involve (a) detailed descriptions of the event, (b) direct challenging of beliefs, (c) extended exposure, or (d) homework’ (World Health Organization, 2013, p. 1). Furthermore, EMDR seems to work faster (often < 8 sessions at 45–60 min; Beer and De Roos, 2017) than traditional TF-CBT (8–12 sessions at 90 min; van Balkom et al, 2013) and is thus cheaper and more efficient (De Roos et al, 2011, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…A fourth advantage of Bayesian analysis is the treatment of missing data, as applied by de Roos et al (2011), who conducted a randomized controlled trial to compare cognitive behavioral therapy with EMDR in a group of disaster-exposed children. In the intention-to-treat analysis, the authors replaced outcome data that were missing owing to dropouts using multiple imputations by fully conditional specification using the MICE package (Van Buuren & Oudshoorn, 1999).…”
Section: Reasons For Using Bayesian Statisticsmentioning
confidence: 99%